We learn from the movement - Portillo Mendoza, Marylin Esmeralda (2020)
The objective of this article is to present how the movement learns to potentiate the teaching-learning process. In this incessant search to improve the teaching practice and find the best strategy, we will rely on the findings made by neuroscience. Without a doubt that the student when making movements is increasing their cerebral plasticity this in turn allows to increase the neurological connections in our brain, developing a greater synapse, improving the capacity of long-term memory, oxygenates the brain, increases the imagination necessary to solve problems, right decisions are made, students have more control of themselves, the right side of our brain is exploited, the same that secretes chemical substances that improve attention and concentration, to receive greater oxygenation we enter a state of relaxation, satisfaction, joy, the learning that is achieved in these moments of movement are significant.